1997
DOI: 10.1086/303867
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Broad Emission‐Line Region in NGC 5548: Hydromagnetic Wind Model versus Observations

Abstract: We analyze the results of long-term observations of broad-line region (BLR) in the Seyfert 1 galaxy NGC 5548 and provide a critical comparison with the predictions of a hydromagnetically-driven outflow model of Emmering, Blandford and Shlosman. We use this model to generate a time series of C IV line profiles that have responded to a time varying continuum. Our modifications to the model include cloud emission anisotropy, cloud obscuration, a CLOUDY-generated emissivity function and a narrow-line component whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 60 publications
5
124
0
Order By: Relevance
“…The model was also applied to the formation and dynamics of BELR clouds by Emmering et al (1992) and Bottorff et al (1997). Emmering et al suggested that dusty material is initially rudiutively driven off the surface of the disk.…”
Section: Hydromagnetic Flowsmentioning
confidence: 99%
“…The model was also applied to the formation and dynamics of BELR clouds by Emmering et al (1992) and Bottorff et al (1997). Emmering et al suggested that dusty material is initially rudiutively driven off the surface of the disk.…”
Section: Hydromagnetic Flowsmentioning
confidence: 99%
“…It has been suggested that Hβ and CIII] might arise from an optically-thick disk, and C IV and Lyα may be produced in a high-ionization wind (Murray & Chiang 1998, Bottorff et al 1997, Königl & Kartje 1994. If the emission lines are produced by different kinematic gas components, then a direct kinematic interpretation of their FWHM is not reasonable.…”
Section: Spectral Principal Component Analysesmentioning
confidence: 99%
“…The physical conditions in BLR are constrained by relative line intensities (see Osterbrock & Ferland (2006), sections 13.6 and 14.5, and references therein). BLR gas is often viewed as some sort of a wind produced by the accretion disc (see Bottorff et al 1997 and references therein) though there is strong observational evidence for inward-directed motions in BLRs (Doroshenko et al 2012;Grier et al 2013). The BLR size measured through reverberation mapping depends on the quasar UV luminosity LUV as RBLR,17 ∼ 1 × L 1/2 UV,45 (Kaspi et al 2007).…”
Section: Introductionmentioning
confidence: 99%